Control interno contable del Gobierno Autónomo Descentralizado Municipal del cantón Alfredo Baquerizo Moreno en el periodo 2019 – 2020. - Márquez Salazar, Tarquino Andree (2022)
The objective of this case study is to analyze the internal accounting control of the Municipal Autonomous Decentralized Government of the Alfredo Baquerizo Moreno Canton in the period 2019 - 2020, the internal accounting control seeks to establish the process of collecting, classifying and observing the registry of operations of the entity and evaluate the results, plan and give opinions on decision making that contribute to the achievement of the entity's goals, this is carried out through the technique of an interview, as part of the research instruments applied in this study. In each case, the investigative line of Financial, Tax and Social Commitment Management and its Audit and Control sub-line are taken into account, to delimit the influence of an internal accounting control in the entity. Within the case study, it was possible to identify several problems that affect the entity, such as the misapplication of internal control procedures and the non-registration of transactions at the time they occur, which in one way or another are they find flaws in the Statement of Financial Situation and these cause the non-compliance of the goals of the institution. My approach in this case study is to review and identify the accounting internal control procedures that the Municipal Autonomous Decentralized Government of the Alfredo Baquerizo Moreno canton has to give recommendations so that they have a correct use of the regulations.